Effect of a physical barrier on adult emergence and egg survival associated with the fungus gnat, Bradysia sp. nr. coprophila (Diptera: Sciaridae), under laboratory conditions - Raudenbush, Amy L.; Cloyd, Raymond A.; Echegaray, Erik R. (My University, 2014)
This study was conducted to assess the direct and indirect effects of Growstones™ aggregates, which are made from recycled glass, on fungus gnat, Bradysia sp. nr. coprophila (Diptera: Sciaridae), adult emergence, female egg-laying capacity, and egg survival. A series of experiments were performed under laboratory conditions to evaluate the effect of different sizes (2.0 to 10.0 mm) of Growstones™ aggregates, layer thicknesses (0.63 to 3.18 cm), and the use of the biological control agent, the rove beetle, Dalotia coriaria, along with different thicknesses (1.27 and 3.18 cm) of small Growstones™ aggregates on fungus gnat adult emergence. For each experiment, Growstones™ aggregates were applied to the surface of the growing medium in 473-mL polypropylene deli containers. This study demonstrated that the thickest (3.18 cm) layer of small (2.0 mm) Growstones™ aggregates significantly reduced or delayed the emergence of fungus gnat adults. In addition, the thickest layer of small Growstones™ aggregates may have indirectly affected egg survival. However, the use of Growstones™ along with rove beetle adults did not significantly reduce fungus gnat adult emergence.
Citation: Raudenbush, Amy L., Raymond A. Cloyd, and Erik R. Echegaray. 2014. “Effect of a Physical Barrier on Adult Emergence and Egg Survival Associated with the Fungus Gnat, Bradysia Sp. Nr. Coprophila (Diptera: Sciaridae), under Laboratory Conditions.” HortScience 49 (7): 905–10. https://doi.org/10.21273/HORTSCI.49.7.905.
Keywords: Fungus gnat; Bradysia sp. nr. coprophila; Adult emergence; Growstones™; Egg survival